PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR MATEMATIKA - Bonok, Zainudin; Bagu, Yusuf (Jurnal Sainstek, 2010)
The research goal is to obtain the following data, (1) difference in mathematics learning outcomes of students who follow the model of cooperative learning with the type of think pair square with mathematics learning outcomes of students who follow the model of cooperative learning with the type of teams games tournaments. (2) The difference between the mathematics learning outcomes of students who use the cooperative model types think the pair square with learners who use the cooperative model type teams games tournaments, when viewed from the learners who have high motivation to learn mathematics. The results showed that There is a difference between the results of learners studying mathematics are taught by cooperative learning model types think the pair square with mathematics learning outcomes of students taught by cooperative learning model type teams games tournaments. For learners who have wanted to learn mathematics is high, the results of learning mathematics learners who are taught to think the type of cooperative learning model square pair was lower than the results of learners studying mathematics are taught by cooperative learning model type teams games tournaments. Keywords: modeling, learning, cooperative learning results